ANALISIS FAKTOR DETERMINAN RETURN ON ASSET PADA PERUSAHAAN PEERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2018-2022 - Said, Sri Wahyuni (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya, 2024)
The aim of this research is to determine the effect of Capital Adequascy Ratio (CAR), Loan to Deposit Ratio (LDR), Net Intrest Margin (NIM), Non Performing Loan (NPL), and Operating Costs and Operating Income (BOPO) on Return On Asset (ROA). This research is quantitative research. The population in this research is banking companies listed on the Indonesia stock Exchange 2018-2022. The sampling technique uses the period sampling method. The samples used in this research were 154. The data used was secondary data and was collected via internet information. The data analysis technique used is multiple linear analysis using the SPSS version 25 program. The results of this study show that the Capital Adequascy Ratio (CAR) variable has a significant positive effect on Return On Asset (ROA), Loan to Deposit Ratio (LDR) has a significant positive effect on Return On Asset (ROA), Net Intrest Margin (NIM) has a positive effect on Return On Asset (ROA), Non Performing Loan (NPL) has a negative effect on Return On Asset (ROA) and Operating Costs and Operating Income (BOPO) has a significant negative effect on Return On Asset (ROA).